2000
DOI: 10.1093/toxsci/56.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity Studies of Benzidine and Its Analogs: Structure-Activity Relationships

Abstract: The Ames Salmonella/microsome assay was employed to test the mutagenicity of benzidine and its analogs using strains TA98 and TA100 in the presence and absence of Aroclor 1254-induced rat S9 mix. 3,3'-Dichlorobenzidine-2HCl and 4,4'-dinitro-2-biphenylamine were directly mutagenic to TA98, while 4,4'-dinitro-2-biphenylamine was directly mutagenic to both TA98 and TA100 in the absence of S9 mix. 2-Aminobiphenyl, 3-aminobiphenyl, and 3,3'-5,5'-tetramethylbenzidine were not mutagenic in either strains in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Murata et al [2001] demonstrated that the N-hydroxy derivative of 4-Ab had the ability to produce oxidative DNA adducts, including 8-OHdG. Chung et al [2000] reported on the mutagenicities of Bz and its analogues. In the presence of S9 mix, 4-Ab, Bz, 3,3 0 -dichlorbenzidine-2HCl, 3,3 0 -dimethoxybenzidine, and 4,4 0 -dinitro-2-biphenylamine were mutagenic to TA98, and 4-Ab, 3,3 0 -dichlorobenzidine-2HCl, 3,3 0 -dimethoxybenzidine, and 4,4 0 -dinitro-2-biphenylamine were mutagenic in TA100.…”
Section: Discussionmentioning
confidence: 99%
“…Murata et al [2001] demonstrated that the N-hydroxy derivative of 4-Ab had the ability to produce oxidative DNA adducts, including 8-OHdG. Chung et al [2000] reported on the mutagenicities of Bz and its analogues. In the presence of S9 mix, 4-Ab, Bz, 3,3 0 -dichlorbenzidine-2HCl, 3,3 0 -dimethoxybenzidine, and 4,4 0 -dinitro-2-biphenylamine were mutagenic to TA98, and 4-Ab, 3,3 0 -dichlorobenzidine-2HCl, 3,3 0 -dimethoxybenzidine, and 4,4 0 -dinitro-2-biphenylamine were mutagenic in TA100.…”
Section: Discussionmentioning
confidence: 99%
“…DCB was mutagenic in TA98, TA100, TA98/1,8-DNP6, TA1535, TA1537, and TA1538 with S9 mix, and the highest potency was detected in TA98 (20)(21)(22)(23)(24). In this study, DCB was revealed to be highly mutagenic in YG1024, Oacetyltransferase-overproducing derivative of TA98, with S9 mix, and its activity was about 50 times as high as that in TA98 with S9 mix (Table 2).…”
Section: Discussionmentioning
confidence: 54%
“…Mutagenicity of DCB: It has been revealed that DCB is mutagenic in S. typhimurium TA98, TA100, and some other strains with and/or without S9 mix (20)(21)(22)(23)(24), and that the most potent mutagenicity was detected in TA98 with S9 mix. However, there was no report on the mutagenicity of DCB in S. typhimurium YG1024, an O-acetyltransferase-overproducing deriva- tive of TA98.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that DCB is mutagenic in Salmonella typhimurium TA98, TA100, TA1535, TA1537, and TA1538 with the presence of the S9 metabolic enzyme activation system [Garner, 1975;Lazear and Louie, 1978;Lazear et al, 1979;Booth et al, 1980;Vithayathil et al, 1983;Prival et al, 1984;Reid et al, 1984;Gentile et al, 1985;Iba, 1987;Lang and Iba, 1987;Messerly et al, 1987;Chung et al, 2000]. Among all dihalogenated benzidines, it is shown that DCB is the most mutagenic [Savard and Josephy, 1986].…”
Section: Introductionmentioning
confidence: 92%